2008
DOI: 10.26530/oapen_459083
|View full text |Cite
|
Sign up to set email alerts
|

Dreamtime Superhighway (TA27) : Sydney Basin Rock Art and Prehistoric Information Exchange

Abstract: Terra Australis reports the results of archaeological and related research within the south and east of Asia, though mainly Australia, New Guinea and island Melanesia -lands that remained terra australis incognita to generations of prehistorians. Its subject is the settlement of the diverse environments in this isolated quarter of the globe by peoples who have maintained their discrete and traditional ways of life into the recent recorded or remembered past and at times into the observable present. List of vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(93 citation statements)
references
References 78 publications
(173 reference statements)
5
81
0
6
Order By: Relevance
“…Franklin (2004) confirmed a number of 'Simple Figurative' styles operating at the regional level across Australia. It is generally assumed that these regional style provinces represent the art of defined culture blocs (sensu Peterson 1976) as various regional studies have demonstrated (McDonald 2008;Morwood 1984;Ross 2013). At a general level there are visual similarities between Port Hedland's and Sydney's art assemblages.…”
Section: Two Rock Art Style Provinces: Sydney Basin and Port Hedlandmentioning
confidence: 99%
See 3 more Smart Citations
“…Franklin (2004) confirmed a number of 'Simple Figurative' styles operating at the regional level across Australia. It is generally assumed that these regional style provinces represent the art of defined culture blocs (sensu Peterson 1976) as various regional studies have demonstrated (McDonald 2008;Morwood 1984;Ross 2013). At a general level there are visual similarities between Port Hedland's and Sydney's art assemblages.…”
Section: Two Rock Art Style Provinces: Sydney Basin and Port Hedlandmentioning
confidence: 99%
“…Both style regions are defined as being 'Simple Figurative' with the art consisting mostly of identifiable animal, human and material culture motifs depicted in a relatively simple schema (Maynard 1979;McCarthy 1962;and see Franklin 2004 for an analysis of these Simple Figurative styles). Both art provinces are probably Holocene manifestations (Attenbrow 2010;Clune and Harrison 2009;McDonald 2008). For both regions we have limited linguistic and ethnographic information about the social groups that produced the rock art.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…tula adzes, cylcons), burials, rock art and biology, and attempts have been made to utilise the results to extrapolate past territorial organisation (e.g. David 1991;David and Chant 1995;David and Cole 1990;Franklin 2004;McDonald 2008;Pardoe 1988Pardoe , 1994Pardoe , 1995Wade et al 2011). With respect to mortuary practices, any regional patterning present may be strongly dependent on external-rather than cultural-factors such as the presence of trees suitable for burial or excarnation (flesh removal), a soft substrate into which to dig a grave, or rockshelters for placement of bundles.…”
Section: Discussionmentioning
confidence: 99%